Frovatriptan versus zolmitriptan for the acute treatment of migraine with aura: a subgroup analysis of a double-blind, randomized, multicenter, Italian study - Tullo, Vincenzo; Allais, Gianni; Curone, Marcella; Ferrari, Michel D.; Omboni, Stefano; Benedetto, Chiara; Colombo, Bruno; Zava, Dario; Bussone, Gennaro (Neurological sciences, 2012)
Migraine with aura affects ~20–30 % of migraineurs and it is much less common than migraine without aura. The aim of this study was to compare the efficacy of frovatriptan 2.5 mg and zolmitriptan 2.5 mg in the treatment of migraine with aura. Analysis was carried out in a subset of 18 subjects with migraine with aura (HIS criteria) out of the 107 enrolled in a multicenter, randomized, double-blind, cross-over study. According to the study design, each patient had to treat three episodes of migraine in no more than 3 months with one drug, before switching to the other treatment. The rate of pain-free episodes at 2 h was significantly ( p < 0.05) larger under frovatriptan (45.8 %) than under zolmitriptan (16.7 %). Pain free at 4 h, pain relief at 2 and 4 h and recurrent episodes were similar between the two treatments, while sustained pain-free episode was significantly ( p < 0.05) more frequent during frovatriptan treatment (33.3 vs. 8.3 % zolmitriptan). Our study suggests that frovatriptan is superior to zolmitriptan in the immediate treatment of patients with migraine with aura, and it is capable of maintaining its acute analgesic effect over 48 h.